The Order of St. John of Jerusalem in the Ribera of Tudela - Fortún Pérez de Ciriza, Luis Javier (Huarte de San Juan. Geografía e Historia, 2011)
It was created to assist pilgrims at a Jerusalem hospital (in the second half of eleventh century), it was officially recognized by Pope (1113) and it early acquired military character, as well as welfare. To finance its activity received donations from all Europe, in Navarre since 1120. The Grand Priory of Navarre had 25 parcels, including 5 in the Ribera region: Cabanillas, Calchetas, Tudela, Fustiñana and Buñuel. Ribaforada was added, from the Templars. We study the formation and setting all of its assets in the Middle Ages. Since 1487 Tudela hosted the Grand Prior of Navarre. In the modern age these parcels had a dual purpose. Calchetas was deserted and uninhabited and its lands were given to ground rent, without major problems. In contrast, the populated Dominion had abundant conflicts (Specially Cabanillas, Fustiñana and Ribaforada), both by jurisdiction and exploitation of the land, as by the government of their parish churches, to the confiscation of 1836.
Keywords: Order of St. John of Jerusalem; military orders; grand priory of Navarre; feudalism; church history